2016
DOI: 10.1002/jcph.848
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a Single Oral Dose of the MEK1/2 Inhibitor Selumetinib in Subjects With End‐Stage Renal Disease or Varying Degrees of Hepatic Impairment Compared With Healthy Subjects

Abstract: Two phase I open‐label studies were conducted to investigate the pharmacokinetics (PK), safety, and tolerability of single oral doses of selumetinib in subjects with end‐stage renal disease (ESRD) undergoing hemodialysis and subjects with varying degrees of hepatic impairment; both studies included a matched control group comprised of healthy individuals. In the renal impairment study, subjects received single doses of selumetinib 50 mg; those with ESRD received selumetinib before and after dialysis (with a be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…The PI3K inhibitor (PI3Ki) buparlisib (BKM120) and the MEK inhibitor (MEKi) selumetinib (AZD6244) were purchased from MedChem Express (Monmouth Junction, NJ) or Chemietek (Indianapolis, IN) and dissolved in dimethyl sulfoxide (DMSO). In single-dose pharmacokinetics studies in human patients, maximum observed plasma concentrations for buparlisib and selumetinib were 2–5 μM (1–2 μg/mL) and 1.1–2.0 μM (0.5–0.9 μg/mL), respectively [ 39 , 40 ]. Depending on experimental requirements, drugs were used at or above these clinically relevant dose ranges.…”
Section: Methodsmentioning
confidence: 99%
“…The PI3K inhibitor (PI3Ki) buparlisib (BKM120) and the MEK inhibitor (MEKi) selumetinib (AZD6244) were purchased from MedChem Express (Monmouth Junction, NJ) or Chemietek (Indianapolis, IN) and dissolved in dimethyl sulfoxide (DMSO). In single-dose pharmacokinetics studies in human patients, maximum observed plasma concentrations for buparlisib and selumetinib were 2–5 μM (1–2 μg/mL) and 1.1–2.0 μM (0.5–0.9 μg/mL), respectively [ 39 , 40 ]. Depending on experimental requirements, drugs were used at or above these clinically relevant dose ranges.…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacokinetics (PK) of selumetinib have been evaluated both in healthy subjects and patients with various tumours . Approximately dose‐proportional PK were observed for selumetinib doses up to 100 mg twice daily , and 75 mg twice daily was established as the maximum tolerated dose for selumetinib .…”
Section: Introductionmentioning
confidence: 99%
“…Selumetinib drug–drug interactions (DDIs), bioavailability, food effects, and hepatic and renal impairment effects have been evaluated in multiple clinical pharmacology studies . The objectives of the current analysis were to develop a population PK model of selumetinib and its N‐desmethyl metabolite in healthy subjects, following oral and IV administration of selumetinib, and to evaluate the influence of covariates on the population PK parameters of selumetinib and N‐desmethyl selumetinib.…”
Section: Introductionmentioning
confidence: 99%
“…Additional safety and tolerability data for the Western studies are reported in detail elsewhere and include references [2022]. …”
Section: Methodsmentioning
confidence: 99%